2018
DOI: 10.1155/2018/6947612
|View full text |Cite
|
Sign up to set email alerts
|

Condylar Degradation from Decreased Occlusal Loading following Masticatory Muscle Atrophy

Abstract: Objective The masticatory muscles are the most important contributor to bite force, and the temporomandibular joint (TMJ) receives direct occlusal loading. The present study aimed to investigate condylar remodeling after masseter muscle atrophy in rats. Methods Sixty 5-week-old female Sprague-Dawley rats were divided into the following 3 groups: the control group, soft diet (SD) group, and botulinum toxin (BTX) group. The cross-sectional area (CSA) of the masseter muscles was investigated as well as atrogin-1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…In this study, significant bone loss of BoNTA‐right condyles was observed after 2 weeks. This is consistent with the potential mandibular bone deterioration after BoNTA intervention suggested by studies in humans and demonstrates that the degradation of the mandibular condyle is established earlier than reported by other studies using female mice, male and female rats and female rabbits . These animal studies only assessed bone tissue after 4 weeks and later.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, significant bone loss of BoNTA‐right condyles was observed after 2 weeks. This is consistent with the potential mandibular bone deterioration after BoNTA intervention suggested by studies in humans and demonstrates that the degradation of the mandibular condyle is established earlier than reported by other studies using female mice, male and female rats and female rabbits . These animal studies only assessed bone tissue after 4 weeks and later.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, during this initial phase, nerve sprouting is evident in the lower limb muscles of rats, the levator auris longus muscle from the neck of mice and the masseter muscle of non‐human primates, which may explain the early masticatory function recovery seen in adult rodents after 10 days . After one single injection, BoNTA rapidly paralyses the masseter, followed by a severe loss of muscle mass . If this BoNTA‐induced masseter muscle atrophy is performed during rodent development, the subchondral bone of the mandibular condyle is deteriorated after 4 weeks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in bone remodeling processes of the samples from the experimental side was detected in young adult female mice as a decrease in both osteoclast activity (measured with TRAP staining) [63,66] and bone mineralization (assessed through alkaline phosphatase staining and fluorescent dyes for mineralized bone) after four weeks [63]. In contrast to these findings, Shi et al reported, in adult female rats, a significant increase of the TRAP staining in the subchondral bone of mandibular condyles four weeks after bilateral injection of BoNT/A in the masseter muscles, when compared with samples from animals bilaterally injected with saline solution [64]. However, different techniques were implemented to assess TRAP staining: In the samples from mice [63,66], a fluorescent approach was employed using TRAP-positive pixels for quantification, whereas the study with rats used an immunohistochemical procedure with multinucleated positive TRAP cells quantitation [64].…”
Section: Resultsmentioning
confidence: 99%
“…The representative of this group is the Digastric (Anterior and Posterior) muscle. The main difference between the human and rat temporomandibular articulation is the biomechanics of movement and the type of incident load resulting from the different nutritional diets among species, albeit a static load is essential for the growth and maintenance of the temporomandibular joint 19–22 . Therefore, physiological experiments have some limitations.…”
Section: Introductionmentioning
confidence: 99%